Transformasi Fikih Munakahat tentang Hukum Menikahi Wanita Ahli Kitab ke dalam Kompilasi Hukum Islam Pasal 40 Huruf (C) - Ilham Mujahid (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2019)
There are three elements examined in this article, namely: legal transformation, Islamic law, and compilation of Islamic law. Legal transformation is a change of law from a legal system to another legal system with characteristics that are not the same so that it changes shape, nature and substance. Islamic law question is the dimension of marriage fiqh which is transferred to the Compilation of Islamic Law, with the process of national legislation. The substance of Jurisprudence about the prohibition of marrying expert women of the Book from the books of Jurisprudence became the focus of the study, then traced how the transformation process into the Compilation of Islamic Law Article 40 letter (c).